Molecular Characterization of 25 Mango Germplasm Using RAPD Markers Available in the South-western Region of Bangladesh - Hossain, M. A.; Islam, M. M.; Mannan, M. A.; Roy, S. K.; Shil, P. (International Journal of Bio-resource and Stress Management, 2023)
RAPD (Randomly amplified polymorphic DNA) markers were used for the genetic variation and relationship analysis among 25 Mango (Mangifera indica L.) germplasm (Gp). PCR amplification with seven primers generated 48 reproducible, clear and distinct bands, out of which 46(95.92%) bands are considered polymorphic and the remaining 2 fragments (4.08%) monomorphic. RAPD matrix of the 25 germplasm of mango using seven primer were assembled for statistical analysis the sizes of the fragments were estimated using DNA 1 kb and 100 bp ladder by electrophoresis with the PCR products.The average polymorphism in all the 25 cultivars using the seven primers was found to be 95.92%. Among all the primers AL 07, OPO 07, OPK 14, OPG 17 and OPA 06 have shown 100% polymorphism while OPH 15 and OPF 08 were found to be least polymorphism (85.71%). The UPGMA (Unweighted Pair Group Method of Arithmetic Mean) dendrogram based on Jaccard’s similarity coefficient segregated the 25 mango germplasm into two clusters. The dendrogram shows that all the germplasm were grouped into two major clusters 16 mango germplasm in one groups and rest 9 mango germplasm is another group. The values of pair-wise comparisons of Nei’s (1979) genetic distance among 25 mango genotypes were computed from 0.043 to 0.510. Comparatively the highest genetic distance 0.510 was found between Gp no. 52 (Langra) vs. Gp73 (Hybrid-10).The lowest genetic distance was found between Gp no. 50 (0.043) (Bhut Bomby) and Gp no. 52 (Langra). Results from the given study would be useful breeders for further improvement of mango varieties.